2020
DOI: 10.4103/ijmbs.ijmbs_139_20
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan fasting in health and disease (2019): A narrative review

Abstract: Introduction: Literature on the health aspects of Ramadan fasting (RF) is widespread in many journals, making it less readily available to those interested in the subject. Materials and Methods: This is a narrative, nonsystematic review of international literature from two major online databases (viz., Scopus and PubMed) in 1 year (2019). The search term “RF” was used, and relevant literature was narrated in a concise thematic account excluding diabetes. Results: The publications spanned the fundamental, clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…20 These foods are high in fiber, vitamins, and minerals, and may have antiinflammatory properties that can help reduce esophageal inflammation and GERD symptoms. 21,22 In addition, the Mediterranean diet is known to be associated with a lower risk of cardiovascular disease, which may also have beneficial effects on GERD symptoms. 3,6,23 Our study also found that both dietary interventions led to significant improvements in quality of life for patients with GERD.…”
Section: Discussionmentioning
confidence: 99%
“…20 These foods are high in fiber, vitamins, and minerals, and may have antiinflammatory properties that can help reduce esophageal inflammation and GERD symptoms. 21,22 In addition, the Mediterranean diet is known to be associated with a lower risk of cardiovascular disease, which may also have beneficial effects on GERD symptoms. 3,6,23 Our study also found that both dietary interventions led to significant improvements in quality of life for patients with GERD.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the extensive number, articles on diabetes were submitted separately elsewhere and were excluded from the present manuscript. [6] The selected articles were reviewed and narrated thematically to provide reasonably concise but adequate representative reading material. Only fulltext research articles and systematic reviews-meta analyses in English were included.…”
Section: Methodsmentioning
confidence: 99%
“…The literature published in 2017-2019 has been reviewed previously. [4][5][6] The present article aims to provide a thematic overview of the global research work in 2020. For practical reasons, the narrations of the diabetes-related literature of 2019 and 2020 were published separately.…”
mentioning
confidence: 99%
“…These "year in review" articles have been a regular feature of their activities since 2018. [1][2][3][4] Many found them useful in bringing together all the years of work under a single cover. Also, Habas et al provided a comprehensive review and update on sodium-glucose cotransporter 2 inhibitors' mechanism of action and use in the high-risk group of kidney transplantation recipients.…”
mentioning
confidence: 99%